Risk Analysis of Heritage Building in Jakarta - Yunita Dian Suwandari; Mawardi Amin; M.Agus Primatama (AIBPM Publisher, 2020)
The purpose of this study is to identify risk factors that influence building safety. The damage suffered by cultural heritage building requires the owner and manager of the building to further improve the supervision of the building safety aspects. This research was conducted in Jakarta and the methods used to identify risks were interviews and questionnaires. Risk analysis uses probability and weight matrices. Finally, there are 23 high risks and the solution can be identified for reducing the risk. The results of this study are beneficial for owners of heritage buildings and the government. Furthermore, the results of this study are also beneficial for academics studying the heritage building field as a literature review.